1993
DOI: 10.1161/01.atv.13.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Protection from atherosclerosis in vein grafts by a rigid external support.

Abstract: Atherosclerosis is a common feature of autogenous vein bypass grafts resulting in their long-term failure. Arterial pressure-induced distension is thought to play a major role in the wall thickening of vein grafts, which may in turn favor atherosclerotic complications. In this study, we evaluated the influence of vein distension on the development of atherosclerotic lesions in jugular vein grafts interposed into the common carotid arteries of rabbits. The proximal half of each vein graft was wrapped with a 4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 21 publications
1
26
0
3
Order By: Relevance
“…Wall motion and stress are to some extent interrelated, and reduction in wall motion probably indicates reduction in cyclic wall stress. External wrapping of vein grafts 17,18 has been studied in detail, but the reduction in the normal wall proliferative response to an arterialized vein due to the external wrap cannot be correlated with the study of arteries and atherogenesis in the presence of hypertension. In addition, wall motion was not measured in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wall motion and stress are to some extent interrelated, and reduction in wall motion probably indicates reduction in cyclic wall stress. External wrapping of vein grafts 17,18 has been studied in detail, but the reduction in the normal wall proliferative response to an arterialized vein due to the external wrap cannot be correlated with the study of arteries and atherogenesis in the presence of hypertension. In addition, wall motion was not measured in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58][59][60] Previous studies showed that relief from increased tensile stress in the vein graft wall by use of a rigid, external support could partially prevent intimal hyperplasia and medial thickening, indicating a role for tensile stress in the regulation of vein graft remodeling. 56 -60 Several recent studies further showed that increased tensile stress induced SMC actin filament degradation and SMC death, 24 influenced the orientation of newly generated SMCs, and might contribute to medial and adventitial hypertrophy in experimental vein grafts.…”
Section: Influence Of Eddy Blood Flow On At 1 Receptor Expressionmentioning
confidence: 99%
“…While the neointimal hyperplasia that occurs in all vein grafts helps to achieve mechanical stability in these otherwise thin-walled conduits, it is believed that this neointima serves as the substrate for the development of atherosclerotic disease. In fact, strikingly better long-term patency rates have been achieved when arterial graft conduits devoid of significant neointima are used in bypass surgery (6 (22)(23)(24). Our "arterialized" grafts not only displayed a structural, biochemical, and mechanical similarity to native arteries but also proved resistant to this accelerated vein graft atherosclerosis.…”
mentioning
confidence: 99%